Nutritional and Therapeutic Analysis of Sethura Laddu for Postpartum Women (International Journal of Ayurveda and Pharma Research, 2025)
Sethura laddu, a traditional Indian sweet consumed by postpartum women, particularly in Uttar Pradesh and Bihar. A well- balanced nutrition is essential for a child's development which is starting from conception and extending through lactation, where maternal nourishment plays a significant role. This analysis aims to verify its role in supporting newly delivered mothers through nutritional and therapeutic perspectives. Sethura laddu is traditionally prepared recipe for recovery of postpartum, using a specific mixture of ingredients, including ginger powder, desiccated coconut, Tikhur powder, deshi ghee, almonds, gond, cashews, raisins, sugar, moong dal powder, makhana, turmeric powder, chironji, and poppy seeds. A detailed nutritional analysis was performed to assess the nutritional composition which is beneficial for postpartum women. The study also included a review of the nutritional benefits. Nutritionally, the laddu provides a balanced combination of proteins, fats, and carbohydrates, contributing to its role in enhancing milk production, reducing back pain, and providing sustained energy. The iron content was quantified as 3.30mg/100g through analysis. Key ingredients such as dry ginger, moong dal powder, Tikhur powder, almonds, and deshi ghee are known for their beneficial effects on digestion, cardiovascular health, lactation, and overall postpartum recovery. Sethura laddu is a nutrient-dense recipe with significant benefits for postpartum women. Its traditional formulation, supported by both historical usage and nutritional analysis, aids in lactation, energy provision, and ease postpartum discomfort. This study highlights the laddu’s value as a dietary supplement for new mothers, combining traditional wisdom with nutritional science to support postpartum health and recovery.